Comparison of variation in the building shapes and the window-to-wall ratio by concerning energy consumption for thermal comfort and lighting - Kurniawan, Andre; Lapisa, Remon; Setiawan, Muhammad Yasep; Rahim, Bulkia; Syahri, Budi (Universitas Negeri Padang, 2023)
Currently, an influential factor contributing to thermal comfort home design is the incorporation of energy-efficient passive design principles. It is exemplified by strategic window placement, the utilization of thermally efficient materials, and effective insulation. It exerts a substantial influence on thermal comfort and electrical consumption. This paper examines the effect of building shape and window-to-wall ratio (WWR) on thermal comfort and lighting energy consumption in residential houses in tropical climates. The lighting electricity and the adaptive thermal discomfort hours of 30 different models of houses were obtained using OpenStudio and EnergyPlus simulation software. The models were developed for three building shapes (square, rectangle, and L-shaped), and each model was varied in five models of window-to-wall ratios. Results indicate that the square-shaped model with a WWR of 10% will provide the lowest energy consumption in thermal comfort had 420.45 kWh/m2. On the other side, the lowest energy consumption in lighting is the square-shaped model with a WWR of 50% had 507.95 kWh/m2. Thus, the recommendation is to use the square-shaped house that represents the most efficient air conditioning system while the other WWR set also produce the most natural luminaire. It is because the percentage of WWR increased will result in more energy consumption in air cooling but slightly lower energy consumption in lighting. However, when considering aesthetics and freshness, the WWR of the 50% model will offer a better deal.